International policy rules and inequality : implications for global economic governance - Ocampo, José Antonio (Initiative for Policy Dialogue at Columbia (Series), 2019)
Over the past decades, the world has seen a dramatic increase in inequality. To what extent have the rules that govern the global economy, formally or informally, affected this trend? How can global governance arrangements be reformed to counteract them?In this book, an interdisciplinary group of prominent scholars scrutinizes how the rules of global economic governance-or the lack thereof-determine the extent and growth of inequality. Economists, political scientists, lawyers, and other experienced contributors bring together cutting-edge research on global rule making and inequality, exploring how international rules can exacerbate inequalities among and within countries to show the crucial interactions between policy choices and the distribution of income and wealth. They provide an in-depth examination of the rules governing foreign-investment protection, cross-border financial flows, and intellectual property rights, as well as the lack of standards governing international taxation and the channels through which they might affect inequality. With a focus on ambitious and achievable reforms, this book offers concrete steps toward global economic governance capable of counteracting inequitable wealth distribution and bringing about fairer economic growth